Pluralism, difference and inequality - Garzón Valdés, Ernesto (Estudios de Filosofía, 2008)
The three concepts mentioned in the title of my presentation are negative referential concepts, that is, they constitute the rejection or departure from supposedly more basic concepts which are -in this case- those of unity, similarity and equality. If this conceptual approach is admitted, I think that it is also possible to admit that the value or disvalue of the former will depend on the conception that one has of the latter. Given that, in turn, similarity and unity can, in a certain way, be referred to equality, I will try here to clarify the concept of equality (I), I will recall some versions of a pluralism that I consider morally and politically unacceptable (II) and, finally, I will propose to distinguish between those inequalities that must necessarily occur in any democratic society and the socio-cultural discriminations typical of totally exclusive regimes (III). [Fragment]